Energy management for cloud computing environment. - Nascimento, Viviane Tavares (2017)
As one of the major energy consumers in the world, the Information and Communication Technology (ICT) sector searches for efficient ways to cope with the energy expenditure of the infrastructure. One of the areas that tend to grow in the coming years, the Cloud Computing services providers look for approaches to change the energy expenditure pattern, concurrently reducing the operational costs. The most common strategy to cope with the energy consumption is related to its efficiency. However, there is the opportunity to encourage a new demand standard, based on the energy supply and price variation. A management approach that takes into account the uctuation of the energy to negotiate the contracts allocation is proposed. Contractible service terms regarding powering the services are established to enable the proposed management approach. Also, a new service layer able to deal with energy requirements is defined as an element of the Cloud Computing environment. Existing literature does not cope with the different terms of the energy supply and does not apply a management of the contracts simultaneously. The proposed method includes a service terms description, the energy-related service layer definition, and a framework for its implementation. A model designed to validate the approach applies a Use Case that simulates Data Centers (DCs) spread through the metropolitan area of S~ao Paulo. The obtained results show the ability of the model to manage the contracts allocation in accordance to the best exploitation of the self-generated energy. Taking into account the assignment costs range, to both user and services provider, the method negotiates the most affordable contracts assignment regarding the energy supply variation.